Improving the Diversity of PSO for an Engineering Inverse Problem using Adaptive Inertia Weight - Shafi Ullah Khan; Obaid Ur Rehman; Naeem Khan; Asfandyar Khan; Syed Anayat Ali Shah; Shiyou Yang (Tehnički Vjesnik, 2018)
Particle swarm optimization is a stochastic optimal search algorithm inspired by observing schools of fishes and flocks of birds. It is prevalent due to its easy implementation and fast convergence. However, PSO has been known to succumb to local optima when dealing with complex and higher dimensional optimization problems. To handle the problem of premutature convergence in PSO, this paper presents a novel adaptive inertia weight strategy and modifies the velocity update equation with the new Sbest term. To maintain the diversity of the population a particular radius r is introduced to impulse cluster particles. To validate the effectiveness of the proposed algorithm, various test functions and typical engineering applications are employed, and the experimental results show that with the changing of the proposed parameter the performance of PSO improves when dealing with these complex and high dimensional problems.